Epigenetic and Transcriptomic Regulation Landscape in HPV+ Cancers: Biological and Clinical Implications - Castro-Oropeza, Rosario; Piña-Sánchez, Patricia (Frontiers in Genetics, 2022)
Human Papillomavirus (HPV) is an oncogenic virus that causes the highest number of viral-associated cancer cases and deaths worldwide, with more than 690,000 new cases per year and 342,000 deaths only for cervical cancer (CC). Although the incidence and mortality rates for CC are declining in countries where screening and vaccination programs have been implemented, other types of cancer in which HPV is involved, such as oropharyngeal cancer, are increasing, particularly in men. Mutational and transcriptional profiles of various HPV-associated neoplasms have been described, and accumulated evidence has shown the oncogenic capacity of E6, E7, and E5 genes of high-risk HPV. Interestingly, transcriptomic analysis has revealed that although a vast majority of the human genome is transcribed into RNAs, only 2% of transcripts are translated into proteins. The remaining transcripts lacking protein-coding potential are called non-coding RNAs. In addition to the transfer and ribosomal RNAs, there are regulatory non-coding RNAs classified according to size and structure in long non-coding RNAs (lncRNAs), circular RNAs (circRNAs), and small RNAs; such as microRNAs (miRNAs), piwi-associated RNAs (piRNAs), small nucleolar RNAs (snoRNAs) and endogenous short-interfering RNAs. Recent evidence has shown that lncRNAs, miRNAs, and circRNAs are aberrantly expressed under pathological conditions such as cancer. In addition, those transcripts are dysregulated in HPV-related neoplasms, and their expression correlates with tumor progression, metastasis, poor prognosis, and recurrence. Nuclear lncRNAs are epigenetic regulators involved in controlling gene expression at the transcriptional level through chromatin modification and remodeling. Moreover, disruption of the expression profiles of those lncRNAs affects multiple biological processes such as cell proliferation, apoptosis, and migration. This review highlights the epigenetic alterations induced by HPV, from infection to neoplastic transformation. We condense the epigenetic role of non-coding RNA alterations and their potential as biomarkers in transformation’s early stages and clinical applications. We also summarize the molecular mechanisms of action of nuclear lncRNAs to understand better their role in the epigenetic control of gene expression and how they can drive the malignant phenotype of HPV-related neoplasia. Finally, we review several chemical and epigenetic therapy options to prevent and treat HPV-associated neoplasms.